Improving Reading Comprehension and Summarising Skills in Primary School: A Quasi-Experimental Study - Antonio Calvani; Antonio Marzano; Lorena Montesano; Marta Pellegrini; Amalia Lavinia Rizzo; Marianna Traversetti; Giuliano Vivanet (LED Edizioni Universitarie, 2023)
MIGLIORARE LA COMPRENSIONE DEL TESTO E LE CAPACITÀ DI SINTESI NELLA SCUOLA PRIMARIA: UNO STUDIO QUASI-SPERIMENTALE Abstract The paper reports the results of the evaluation of a programme aimed at improving reading comprehension and summarising skills of fourth graders through a quasi-experimental study conducted with 671 students (421 in the experimental group and 250 in the control group) in Italian schools. Students assigned to the experimental group received three months of the intervention while students in the control group continued with regular teacher practice. Results showed a statistically significant difference between the two conditions on reading comprehension and summarising skills. Students included in the experimental group outperformed students in the control group in both the measures used (dppc2 = 0.32 in the Summarising Test and dppc2 = 0.54 in the Summary Qualitative Assessment). No differences were found between students with different proficiency vocabulary levels in the experimental group. The implications for research practice and limitations of the study are discussed.